Edukacja uniwersytecka i procesy stratyfikacji społecznej. - Melosik, Zbyszko (Kultura-Społeczeństwo-Edukacja, 2013)
In the article author discusses the relationships between education and social stratification. The theories of meritocracy and credentalism are analyzed and a special attention is paid to the opposition between their interpretations of the equality/inequality dilemma. Then the R. Turner’s concepts of social mobility and E. Hopper’s concepts of social creation of aspiration are presented. In the second part of the article the phenomenon of overeducation and diploma in ation is considered as well as a case of higher education in Japan as a factor of social stratification in this country.